2017
DOI: 10.3389/fnmol.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Association of TrkA and APP Is Promoted by NGF and Reduced by Cell Death-Promoting Agents

Abstract: The amyloid precursor protein (APP) interacts with the tropomyosin receptor kinase A (TrkA) in normal rat, mouse, and human brain tissue but not in Alzheimer’s disease (AD) brain tissue. However, it has not been reported whether the two proteins interact directly, and if so, which domains are involved. Clarifying these points will increase our understanding of the role and regulation of the TrkA/APP interaction in normal brain functioning as well as in AD. Here we addressed these questions using bimolecular fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 68 publications
(99 reference statements)
1
25
0
Order By: Relevance
“…83 This may play a role in the potential of NCs to give rise to tissues of ectodermal and mesodermal (connective) lineages. 80 When contextualized based on a particular OP's germ layer of origin, transcriptomic patterns meet expectations and further support the notion that OP differentiation remained faithful to lineage type.…”
Section: Inhibition Of Fgf1 Reduces Runx2 Expressionsupporting
confidence: 56%
See 1 more Smart Citation
“…83 This may play a role in the potential of NCs to give rise to tissues of ectodermal and mesodermal (connective) lineages. 80 When contextualized based on a particular OP's germ layer of origin, transcriptomic patterns meet expectations and further support the notion that OP differentiation remained faithful to lineage type.…”
Section: Inhibition Of Fgf1 Reduces Runx2 Expressionsupporting
confidence: 56%
“…79 Osteoblastsecreted NGF stimulates nerve sprouting, which points to an interesting crosstalk between the skeletal and nervous systems. 80,81 ANTI-SENSE A2 OF PAPPA (PAPPA-AS2) controls the upstream signaling pathway(s) during adipogenesis. 82 Antisense transcripts cause cisrepression of transcription of their sense counterparts, which usually results in a negative correlation between the two transcriptional states.…”
Section: Inhibition Of Fgf1 Reduces Runx2 Expressionmentioning
confidence: 99%
“…Briefly, once MINUS and PLUS PLA probes are in close proximity, the DNA strands interact and the subsequent addition of two other circle-forming DNA oligonucleotides takes place, leading to DNA amplification reaction, detected by Texas red fluorescence. As previously reported [ 38 ], DIV10 cholinergic neurons were fixed in 4% PFA for 15 min and subjected to in situ PLA according to the manufacture’s instruction (Duolink In Situ Detection Reagents Red kit, Sigma Aldrich, DUO92008). To stain the nuclei dried coverslips were mounted with mounting medium (DUO82040).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated the advantage of using BiFC to detect protein-protein interactions [64,65]. We noticed that the BiFC technology has at least three advantages that are not found with conventional approaches such as yeast-two-hybrid assays or co-immunoprecipitation (co-IP)/mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%